The Effectiveness of Using Digital Literacy to Enhance Student’s Critical Thinking in English Language Teaching - Alfiyan, M (Universitas Batanghari Jambi, 2025)
This study investigates the effectiveness of using digital literacy in english language teaching. The aim of this study is to find out the effectiveness of using media in teaching English language. This research is classified as a type of qualitative research using the literature study method to collect data related to the topic. The result shows that media digital has an effectiveness to teach English language. Besides that, there are several challenges such as a limited access to technology, quality of content, and potential distractions must be overcome to have the benefits of using digital media in learning.